Systematic Review of Digital Interventions for Adolescent and Young Adult Women's Body Image - Mahon, Ciara; Seekis, Veya (Frontiers in Global Women's Health, 2022)
Background: A growing number of digital interventions have been developed to address a range of mental health issues including body image. Identifying effective interventions for body image is important given the prevalence of body image concerns and their associated negative outcomes among young women. This review aimed to critically evaluate current evidence on the use of digital interventions for adolescent and young adult women's body image. Methods: A literature search was performed in November 2021 across three databases, PsychINFO, Web of Science and Pubmed to identify studies published with keywords and synonyms of “body image” and “digital interventions” that have been conducted with girls/women aged 10-25 years. Studies were included if they assessed a universal body image intervention delivered through a digital platform (e.g., web-based, mobile phone) and if they reported body image outcomes using validated measures. Two authors independently screened studies extracted data and assessed the quality of studies. Results: Nine of 15 interventions were effective in improving at least one body image outcome from pre-post intervention; however, effect sizes were mostly small-medium, and few effects were maintained at follow-up. Studies were heterogeneous in terms of delivery format, duration, sample characteristics, quality, and outcomes. Discussion: Findings suggest that digitally delivered interventions can effectively improve some body image outcomes in young women. Characteristics of effective studies are discussed and suggestions for future work on intervention development in this field are provided.